Polychromatic emission in a wide energy range from InP-InAs-InP multi-shell nanowires. (28th February 2019) - Battiato, S; Wu, S; Zannier, V; Bertoni, A; Goldoni, G; Li, A; Xiao, S; Han, X D; Beltram, F; Sorba, L; Xu, X; Rossella, F
Abstract: InP-InAs-InP multi-shell nanowires (NWs) were grown in the wurtzite (WZ) or zincblende (ZB) crystal phase and their photoluminescence (PL) properties were investigated at low temperature (≈6 K) for different measurement geometries. PL emissions from the NWs were carefully studied in a wide energy range from 0.7 to 1.6 eV. The different features observed in the PL spectra for increasing energies are attributed to four distinct emitting domains of these nano-heterostructures: the InAs island (axially grown), the thin InAs capping shell (radially grown), the crystal-phase quantum disks arising from the coexistence of InP ZB and WZ segments in the same NW, and the InP portions of the NW. These results provide a useful frame for the rational implementation of InP-InAs-InP multi-shell NWs containing various quantum confined domains as polychromatic optically active components in nanodevices for quantum information and communication technologies.